Teachers’ Digital Skills Research Trends: A Scopus Bibliometric Study (2020–2025) - Khoerunnisa, Indah; Fathurochman, Alam (IQRO: Journal of Islamic Education, 2025)
The COVID-19 pandemic has catalyzed fundamental changes in educational technology integration, emphasizing the critical importance of teachers' digital competencies beyond emergency remote teaching. This study presents a comprehensive bibliometric analysis of research trends in teachers' digital skills through Scopus-indexed publications from 2020 to 2025. Through systematic document retrieval and screening, we analyzed 1,129 relevant publications using Biblioshiny (R-bibliometrix) and VOSviewer to examine publication patterns, collaboration networks, and conceptual evolution. The findings reveal significant growth in scientific productivity with a compound annual growth rate of 14.94%, characterized by robust international collaboration (16.14% of publications). Thematic analysis identified four major research clusters: digital competency frameworks, pedagogical integration strategies, professional development models, and emerging technological innovations. The intellectual structure demonstrates a clear shift from crisis-response studies toward systematic approaches in digital skill development, with artificial intelligence emerging as a promising research frontier. Our results provide strategic insights for educational policymakers and researchers in designing evidence-based professional development programs and identifying future research directions in educational technology integration. This study contributes to understanding the evolving landscape of teachers' digital competencies in the post-pandemic educational environment.